Mental models in financial markets: How do experts reason about the pricing of climate risk? - Rob Bauer; Katrin Gödker; Paul Smeets; Florian Zimmermann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We investigate financial experts' beliefs about climate risk pricing and analyze how those beliefs influence stock return expectations. In a comprehensive survey, we elicit experts' beliefs using both structured and open-ended questions. We establish that most experts share the view that climate risks are insufficiently reflected in stock prices, yet they hold heterogeneous beliefs about the source and persistence of the mispricing. Through the analysis of open text responses, we delineate distinct mental models used by financial professionals to interpret and predict the asset pricing implications of climate risks. Differences in experts' mental models explain variation in return expectations in the short-term (1-year) and long-term (10-year). Furthermore, we document that experts' political leanings and geography determine the type of mental model they hold. In a last step, we show that one widely held mental model, which is based on second-order beliefs, causally affects experts' return expectations using an information provision experiment.
Keywords: D01; G10; G40; 330; Climate Finance; Climate Risks; Mental Models; 2nd order beliefs; Expectations